Organic Nitrogen Uptake and Assimilation in Cucumis sativus Using Position-Specific Labeling and Compound-Specific Isotope Analysis - Dion, Pierre-Paul; Jämtgård, Sandra; Bertrand, Annick; Pepin, Steeve; Dorais, Martine (Frontiers in Plant Science, 2018)
Organic nitrogen is now considered a significant source of N for plants. Although organic management practices increase soil organic C and N content, the importance of organic N as a source of crop N under organic farming management systems is still poorly understood. While dual-labeled (13C and 15N) molecule methods have been developed to study amino acid uptake by plants, multiple biases may arise from pre-uptake mineralization by microorganisms or post-uptake metabolism by the plant. We propose the combination of different isotopic analysis methods with molecule isotopologues as a novel approach to improve the accuracy of measured amino acid uptake rates in the total N budget of cucumber seedlings and provide a better characterization of post-uptake metabolism. Cucumber seedlings were exposed to solutions containing L-Ala-1-13C,15N or U-L-Ala-13C3,15N, in combination with ammonium nitrate, at total N concentrations ranging from 0 to 15 mM N and at inorganic/organic N ratios from 10:1 to 500:1. Roots and shoots were then subjected to bulk stable isotope analysis (BSIA) by Isotope Ratio Mass Spectrometry (IRMS), and to compound-specific stable isotope analysis (CSIA) of the free amino acids by Gas Chromatography – Combustion – Isotope Ratio Mass Spectrometry (GC-C-IRMS). Plants exposed to a lower inorganic:organic N ratio acquired up to 6.84% of their N from alanine, compared with 0.94% at higher ratio. No 13C from L-Ala-1-13C,15N was found in shoot tissues suggesting that post-uptake metabolism of Ala leads to the loss of the carboxyl-C as CO2. CSIA of the free amino acids in roots confirmed that intact Ala is indeed taken up by the roots, but that it is rapidly metabolized. C atoms other than from the carboxyl group and amino-N from Ala are assimilated in other amino acids, predominantly Glu, Gln, Asp and Asn. Uptake rates reported by CSIA of the free amino acids are nevertheless much lower (16 to 64 times) than those reported by BSIA. Combining the use of isotopologues of amino acids with compound-specific isotope analysis helps reduce the bias in the assessment of organic N uptake and improves the understanding of organic N assimilation especially in the context of organic horticulture.